Підхід до проектування систем пасивної безпеки спортивного автомобіля - Ужва, Анатолій; Шаповаленко, Владислав (КІНПАТРІ ЛТД, 2013)
The analysis of the scheme by which will be built two massive schemes that helps to describe the movement of man in a side impact.
Design approaches systems passive safety of sports car